2018
DOI: 10.1021/acs.jnatprod.7b00835
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression Guides Identification of the Biosynthetic Gene Cluster of Chuangxinmycin, an Indole Alkaloid Antibiotic

Abstract: The indole alkaloid antibiotic chuangxinmycin, from Actinobacteria Actinoplanes tsinanensis, containing a unique thiopyrano[4,3,2- cd]indole scaffold, is a potent and selective inhibitor of bacterial tryptophanyl-tRNA synthetase. The chuangxinmycin biosynthetic gene cluster was identified by in silico analysis of the genome sequence, then verified by heterologous expression. Systemic gene inactivation and intermediate identification determined the minimum set of genes for unique thiopyrano[4,3,2- cd]indole for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Compound 4 is found to be identical to the molecule previously detected from a CxnD knockout strain with its methylation system (M1146/pCAP‐CM( ΔcxnD ), Figure 2 B, vi), which was erroneously deduced as seco‐chuangxinmycin ( 3 ) by HR–MS [11a] . As molecules bearing thiol group(s) from microbial fermentation cultures are often isolated as their derived forms, with thiol group(s) modified or oxidized, [11b, 13] the structure of 4 suggested that ( R )‐3‐(1 H ‐indol‐3‐yl)‐2‐mercaptopropanoic acid ( 5 ) was the authentic substrate of CxnD in 1 biosynthesis in vivo, and CxnD catalyzed the C−S bond formation from a chiral substrate in vivo. Then epimeric 3 (80 % ( 2R , 3S )‐ 3 +20 % ( 2S , 3S )‐ 3 , with the same configuration of the chiral C‐3 as in 1 ) and racemic 5 ( 2R ‐ 5 + 2S ‐ 5 ) were chemically synthesized (Table S3, Figure S3, S18–S28), and, respectively fed into the S. coelicolor M1152 strain expressing CxnD only.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Compound 4 is found to be identical to the molecule previously detected from a CxnD knockout strain with its methylation system (M1146/pCAP‐CM( ΔcxnD ), Figure 2 B, vi), which was erroneously deduced as seco‐chuangxinmycin ( 3 ) by HR–MS [11a] . As molecules bearing thiol group(s) from microbial fermentation cultures are often isolated as their derived forms, with thiol group(s) modified or oxidized, [11b, 13] the structure of 4 suggested that ( R )‐3‐(1 H ‐indol‐3‐yl)‐2‐mercaptopropanoic acid ( 5 ) was the authentic substrate of CxnD in 1 biosynthesis in vivo, and CxnD catalyzed the C−S bond formation from a chiral substrate in vivo. Then epimeric 3 (80 % ( 2R , 3S )‐ 3 +20 % ( 2S , 3S )‐ 3 , with the same configuration of the chiral C‐3 as in 1 ) and racemic 5 ( 2R ‐ 5 + 2S ‐ 5 ) were chemically synthesized (Table S3, Figure S3, S18–S28), and, respectively fed into the S. coelicolor M1152 strain expressing CxnD only.…”
Section: Resultsmentioning
confidence: 84%
“…Thus, 2R ‐ 5 , bearing the same configuration as 4 at chiral C‐2, was the substrate for CxnD both in vitro and in vivo. Although ( 2R , 3S )‐ 3 is also the substrate for CxnD in vitro, the thio‐derivative of 3 was not found in ΔcxnD strains, [11b] indicating the methylation at C‐3 was the last step in 1 biosynthesis. The steady‐state kinetic values were calculated by quantitative analysis of product.…”
Section: Resultsmentioning
confidence: 98%
“…[9] Theu nique tricyclic indole-S-hetero scaffold of 1 attracted the interests of many medicinal chemists and biochemists, [10] but until recently the biosynthetic gene cluster of 1 was identified (Table S1). [11] In the proposed biosynthetic pathway of 1 (Figure 1B), l-Trp is converted to indole-3pyruvic acid by aminotransferase CxnB and then reduced by NAD(P)H-dependent reductase CxnC.A ni nter-molecular C À Sb ond is then formed by hijacking the primary sulfur transfer system, using the cluster-situated sulfur carrier protein CxnE (possibly processed by CxnF). Based on the product analysis from CxnD-disrupted strains, [11] an intramolecular CÀSbond is formed by cytochrome P450 CxnD to generate the tricyclic dihydrothiopyrano[4,3,2-cd]indole scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In the proposed biosynthetic pathway of 1 (Figure 1B), l-Trp is converted to indole-3pyruvic acid by aminotransferase CxnB and then reduced by NAD(P)H-dependent reductase CxnC.A ni nter-molecular C À Sb ond is then formed by hijacking the primary sulfur transfer system, using the cluster-situated sulfur carrier protein CxnE (possibly processed by CxnF). Based on the product analysis from CxnD-disrupted strains, [11] an intramolecular CÀSbond is formed by cytochrome P450 CxnD to generate the tricyclic dihydrothiopyrano[4,3,2-cd]indole scaffold. TheC 3-methylation in 1 biosynthesis is performed by ar adical SAM superfamily protein CxnA coupled with ah ypothetical protein Ats4177.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been proven that most of the genes encoding secondary metabolites in fungi are cryptic under certain culture conditions [8]. In recent years, due to the advances in genome sequencing and bioinformatics-based predictions of encoded natural products in BGCs, it has been enabled to obtain structurally-unique secondary metabolites from fungi with the assistance of genomic information [8,9,10].…”
Section: Introductionmentioning
confidence: 99%